The art of communication a librarian's guide for successful leadership, collaboration, and advocacy - Weisburg, Hilda K. 1942- (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"Teaches strategies and techniques to help librarians build the successful communication skills that are a requirement for leadership"--Provided by publisher.